The outward shift of clarithromycin binding to the ribosome in mutant Helicobacter pylori strains. Issue 6 (14th August 2020) - Salehi, Najmeh; Attaran, Bahareh; Zare‐Mirakabad, Fatemeh; Ghadiri, Bahareh; Esmaeili, Maryam; Shakaram, Mohadeseh; Tashakoripour, Mohammad; Eshagh Hosseini, Mahmoud; Mohammadi, Marjan
Abstract: Objectives: Disruption of protein synthesis, by drug‐mediated restriction of the ribosomal nascent peptide exit tunnel (NPET), may inhibit bacterial growth. Here, we have studied the secondary and tertiary structures of domain V of the 23S rRNA in the wild‐type and mutant (resistant) H. pylori strains and their mechanisms of interaction with clarithromycin (CLA). Methods: H pylori strains, isolated from cultured gastric biopsies, underwent CLA susceptibility testing by E test, followed by PCR amplification and sequencing of domain V of 23S rRNA. The homology model of this domain in H pylori, in complex with L4 and L22 accessory proteins, was determined based on the E. coli ribosome 3D structure. The interactions between CLA and 23S rRNA complex were determined by molecular docking studies. Results: Of the 70 H pylori strains, isolated from 200 dyspeptic patients, 11 (16%) were CLA‐resistant. DNA sequencing identified categories with no (A), A2142G (B), and A2143G (C) mutations. Docking studies of our homology model of 23S rRNA complex with CLA showed deviated positions for categories B and C, in reference to category A, with 12.19 Å and 7.92 Å RMSD values, respectively. In both mutant categories, CLA lost its interactions at positions 2142 and 2587 and gained two new bonds with the L4 accessory protein. Conclusion: Our data suggest that, in mutant H pylori strains, once the nucleotides at positions 2142 and 2587 are detached from the drug, CLA interacts with and is peeled back by the L4 accessory protein, removing the drug‐imposed spatial restriction of the NPET.